Fruit growth and proximate composition of deshi (Diospyros peregrina) and bilati gab (D. discolor) (Journal of the Bangladesh Agricultural University, 2016)
Fruit (berry) growth, maturity and nutritional composition of deshi (Diospyros peregrina Gurke) and bilati Gab (D. discolor Gurke) were investigated at the Botanical Garden of Bangladesh Agricultural University, Mymensingh (24o26' and 24054' N and 90015' and 90030' E) between April and August, 2011. Flowers were tagged at first opening (days after flowering, DAF) and fruit growth was investigated up to maturity. Fruit size (length and diameter), individual fruit weight, AGR and proximate composition of matured fruits were investigated. Morphological and growth parameters were recorded at 7-days interval up to 63 DAF in deshi and 85 DAF in bilati gab. All the morphological characters of fruits were gradually increased with increasing DAF and followed sigmoid pattern. The length and diameter of the berry became 5.80 and 4.61 cm, respectively at 63 DAF in deshi gab, and 9.13 and 7.62 cm, respectively at 85 DAF in bilati gab. The fresh and dry weights of berries were also maximum at 63 DAF in deshi and at 85 DAF in bilati gab. The maximum dry weight of seed i.e. PM in deshi gab attained at 56 DAF and that of bilati gab at 83 DAF. The proximate composition of matured berries of deshi and bilati gab at PM showed little variation between the species and hence, average crude protein, crude fat, ash and total carbohydrate was 5.35, 1.08, 3.74 and 67.47%, respectively. It might be concluded that harvest maturity attained around two months after flowering in deshi gab with yellowish green colour on fruit coat and three months from flowering in bilati gab when fruits turn into deep red colour with average fruit fresh weight of 60 g and 220 g, respectively.J. Bangladesh Agril. Univ. 12(2): 261-266, December 2014